The Role of Psychological Factors in Older Adults' Readiness to Use eHealth Technology: Cross-Sectional Questionnaire Study - Knapova, Lenka; Klocek, Adam; Elavsky, Steriani (Journal of medical Internet research, 2020)
BACKGROUND: Information and communication technology (ICT) use among older adults has been on the rise in recent years. However, the predictors and mechanisms behind older adults' acceptance and use of ICT are not clear. OBJECTIVE: This study aimed to systematically describe ICT usage among Czech older adults and to evaluate the factors influencing their ICT use and readiness to use digital technology to promote health (eHealth readiness). The primary focus was on psychological factors and the role of persons close to older adults. METHODS: The research utilized cross-sectional survey data from a quota-based sample of Czech older adults (>50 years) and persons close to them further referred to as close persons (N=250 dyads). A structural equation modeling framework was used to evaluate relationships between psychological factors, ICT use, and eHealth readiness. RESULTS: Czech older adults' use of ICT is low with the exception of cell phone usage (cell phone usage by 173/250, 69.2%; other devices used by 50/250, 20.0% of older adults or less). Apart from age (β=-.21; P<.001), eHealth readiness was predicted by ICT use (β=.65; P<.001). eHealth readiness was also indirectly affected by the need for cognitive closure (NFCC): individuals with a high need for closure perceived more barriers to ICT (β=.23; P=.01) and more reported barriers were linked to lower ICT usage (β=-.21; P=.001). The expected positive relationships between eHealth readiness of persons close to older adults and ICT use and eHealth readiness of older adults were not significant, but the total effect of eHealth readiness of persons close to older adults on eHealth readiness of older adults was positive and significant (β=.18; P=.01), indicating some level of influence of persons close to them on older adults' attitudes and behaviors. CONCLUSIONS: This study provided the first systematic examination of Czech older adults' ICT usage and eHealth readiness. Novel predictors (NFCC and close persons' variables) were evaluated and yielded actionable results. More research is needed to clarify the role of persons close to older adults.
Keywords: eHealth; information technology; Cross-Sectional Studies; Male; Aging; need for cognitive closure; Aged; mužské pohlaví; senioři; průzkumy a dotazníky; Telemedicine; lidé; ženské pohlaví; Humans; stárnutí; průřezové studie; telemedicína; Female; Surveys and Questionnaires; elderly